Production of Tomato (Solanum lycopersicum L.) in Different Nutrient Regime - Manta, Shreyasee; Choudhuri, Partha; Majumdar, Ranodip (International Journal of Economic Plants, 2024)
A field level investigation was during the month of November, 2021–22 to observe integrated effect of different nutrient sources on growth, yield, quality and economics of tomato. The field work was conducted in Randomized Block Design consisting of eight different nutrient combinations like-Treatment-1: (control), Treatment-2: (100% Recommended Dose of Fertilizer), Treatment-3: [100% Recommended Dose of Fertilizer+15 t Farm yard manure-ha ], Treatment-4 [75% Recommended Dose of Fertilizer+7.5 t ha-1 Farm Yard Manure+Biofertilizer (Phosphate Solubilizing Bacteria+Azotobacter)], Treatment-5 [75% Recommended Dose of Fertilizer+4 t ha-1 vermicompost+Biofertilizers (Phosphate Solubilizing Bacteria+Azotobacter), Treatment-6 [75% Recommended Dose of Fertilizer+2 t ha-1 vermicompost+Biofertilzers (Phosphate Solubilizing Bacteria+Azotobacter)], Treatment-7 [75% Recommended Dose of Fertilizer+0.5 t ha-1 Neem cake+Biofertilizers (Phosphate Solubilizing Bacteria+Azotobacter)], Treatment-8[75% Recommended Dose of Fertilizer+2 t ha-1 Mustardcake+Biofertilizers (Phosphate Solubilizing Bacteria+Azotobacter)]. Combined application of 75% Recommended Dose of Fertilizer+2 t ha-1 vermicompost+Biofertilzers (Phosphate Solubilizing Bacteria+Azotobacter) recorded significantly maximum values for the vegetative parameters.. This treatment also recorded maximum values for number of fruits plant-1 (45.89), fruit weight (35.62 g), yield plot-1 (40 kg) and yield ha-1 (70.08 t) and benefit:cost ratio (2.8). Maximum TSS (4.8°Brix), ascorbic acid (24.05 mg 100 g-1) and lycopene content (4.69 mg 100 g-1) were noticed with 75% Recommended Dose of Fertilizer+4 t ha-1 vermicompost+Biofertilizers (Phosphate Solubilizing Bacteria+Azotobacter). Experiment data showed that combination of 2t ha-1 of vermicompost and mixture of phosphate solubilizing bacteria, Azotobacter along with 75% of recommended dose of fertilizer was proved as beneficial for sustainable production of tomato in new alluvial plains of West Bengal.